Chondrosternal Arthritis in Infant: An Unusual Entity - Athina Nikolarakou; Dana Dumitriu; Pierre-Louis Docquier (Case Reports in Orthopedics)
Primary arthritis of chondrosternal joint is very rare and occurs in infants less than 18 months of age. Presentation is most often subacute but may be acute. Child presents with a parasternal mass with history of fever and/or local signs of infection. Clinical symptoms vary from a painless noninflammatory to a painful mass with local tenderness and swelling, while fever may be absent. Laboratory data show low or marginally raised levels of white blood cells and C-reactive protein, reflecting, respectively, the subacute or acute character of the infection. It is a self-limiting affection due to the adequate immune response of the patient. Evolution is generally good without antibiotherapy with a progressive spontaneous healing. A wait-and-see approach with close follow-up in the first weeks is the best therapeutic option.